Relationships between quality of services and satisfaction, loyalty and “word of mouth” communication: Perception of students at a Higher Education Institution (HEI) during the pandemic - Pompei, Telêmaco; Gouveia , Luís M. Borges (Seven Editora, 2023)
The objective of this study was to evaluate the relationships between service quality, satisfaction, perceived value, loyalty and "word of mouth" in an HEI, pointing to the adoption of new practices in the HEI in question, as post-pandemic competitive alternatives. This is a descriptive and exploratory research, with a qualitative approach. The sample consisted of 100 students from different courses of a private HEI in the state of Minas Gerais, submitted to measurements and analysis of their characteristics and opinions. The results indicated a relative positivity in relation to the HEI, and the women, undergraduates, between 21-23 years of age showed greater satisfaction in relation to the higher education institution. Of all respondents, regarding the quality of services (53%) remained neutral; perceived value in terms of students' needs (50%) in agreement; perceived value to the HEI's performance (46%) neutral; overall satisfaction (45%) equally neutral; satisfaction with the services offered (48%) neutral; option for another HEI, 39% said they would hardly choose another one; pride in the HEI in which they study (48%), “word of mouth” communication (52%); positive comments on social networks (50%). The findings showed that most students remained neutral on most questions, results attributed to the time of the pandemic, when the research was carried out. DOI:https://doi.org/10.56238/emerrelcovid19-066